Phytophthora cinnamomi quantification techniques, root phosphite concentrations and their response to phosphonate application in avocado - Masikane, Siyethemba (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.